FORMAT PENYELENGGARAAN KERJASAMA WAJIB ANTAR DAERAH DALAM PELAYANAN PUBLIK DALAM BIDANG TRANSPORTASI (STUDI KASUS DKI JAKARTA DENGAN BODETABEK): Donri Wahyu Tinambunan - admin, admin (Fakultas Hukum Universitas Islam Jakarta, 2017)
This research discusses about how to implement mandatory cooperation cooperation between regions of DKI Jakarta practices in public service in transportation field, and what is the ideal format for the implementation of mandatory interregional cooperation in public service in the field of transportation. The methodology used is juridical-normative research with a focus on approaching the concept, conceptual, historical, comparative and case. By using secondary data were analyzed using qualitative and descriptive analysis. The results of this research are: Firstly, Implementation of mandatory interregional cooperation in public service is less efficient and less effective because Jabodetabek BKSP only has the authority to coordinate and facilitate but not authorized to make decision. Secondly, the ideal format for the implementation of mandatory interregional cooperation in the public transportation sector in DKI Jakarta for the future uses the format of the Regional Special District and Authorities model.